Dummy Location Generation Algorithm for User Density - LI Menghan; FANG Wei; LI Lihong (Journal of Harbin University of Science and Technology)
With the development of the Internet, location-Based Services have become an indispensable part of people's lives. However, the issue of user location security has also gained significant attention. To address this issue, this article proposes a user density-based location privacy protection algorithm. The algorithm utilizes the distribution density of surrounding users to determine suitable anonymous areas and divides the areas into multiple anonymous sub-areas. Additionally, it combines probability distribution to generate dummy locations, thereby protecting the privacy of user locations. Experimental verification shows that under the same conditions, the algorithm only requires awareness of 3 to 4 jumps to determine anonymous areas. Furthermore, when the anonymity degree is set at 40 , the relative area ratio and relative anonymity degree remain in a balanced state. This algorithm not only effectively controls the area of anonymous regions and reduces algorithm costs but also protects user location privacy. It demonstrates practicality and feasibility.